Association of Immunologic Markers With Survival in Upfront Resectable Pancreatic Cancer - Tang, Ephraim S. (JAMA Surg, 2018)
This cohort study assesses the association of immunologic variables and survival in patients with resectable pancreatic ductal adenocarcinoma.